An Overall Concept on Pre and Probiotics - M. Keerthi; AVS Rajeswari; K Deekshitha (Contemporary Research and Perspectives in Biological Science Vol. 3, 2024)
The gut of the human body contains several microorganisms which are collectively known as gut microbiota, microbiome, or Intestinal microflora. Prebiotics and probiotics help in the qualitative and quantitative improvement of microbiome thereby favoring many health benefits if taken through diet or as formulation. The marketing scale of pre and probiotics is being increased day by due to the health benefits shown by them in consumers. The awareness needed to be increased among people regarding the use of pre-and probiotics.